Business Planning : Pitaberry Enterprise / Nurul Aina Che Arifin ...[et al.] - Che Arifin, Nurul Aina; Abdul Rahim, Siti Safuhah; Basri, Siti Rokiah; Hang Tuah, Syazwani (2009)
Marketing is one of the important things in the business. Marketing can be define as the process of planning, pricing, promoting and distribution of ideas, goods and services to create exchange that satisfy individual and organization goals. Beside that, two aspects to know about marketing is, first it is a philosophy, an attitude, a perceptive, or met organization that stress customer’s satisfaction. Second is a set of activities to use to implement these philosophies. Philosophies we can refer it as production, sales, market and society marketing orientations. To become the successful organization, the organization needs to have marketing strategy and market segmentation is the key in developing marketing strategy. This market segmentation helps the organization to define what customers need. Market segmentation is the process of dividing a market into meaningful, relative similar, and identifiable segment or group